Anti-proliferative activity of a purified polysaccharide isolated from the basidiomycete fungus Paxillus involutus. (1st February 2018) - Barad, Ankush; Mackedenski, Sebastian; Li, Wai Ming; Li, Xiao Jie; Lim, Bryan Chu Chwen; Rashid, Faran; Tackaberry, Linda E.; Massicotte, Hugues B.; Egger, Keith N.; Reimer, Kerry; Cheung, Peter C.K.; Lee, Chow H.
Highlights: Polysaccharide (GIPinv) with anti-cancer activity was purified from Paxillus involutus . GIPinv is 229 kDa and is a heteroglycan. GIPinv has mixed linkages and a degree of branching of 0.38. GIPinv exerts its anti-proliferative activity through induction of apoptosis. GIPinv inhibits growth of seven different cancer cell lines. Abstract: A growth-inhibitory polysaccharide (GIPinv) was purified using size-exclusion and ion-exchange chromatography from the fourth sodium hydroxide extraction step of a fungus found in British Columbia. The fungus was genetically identified as a member of the Paxillus involutus complex. GIPinv has an average molecular weight of 229 kDa and is a heteroglycan composed of glucose (65.9%), galactose (20.8%), mannose (7.8%), fucose (3.2%) and xylose (2.3%). GC–MS methylation analysis suggests that GIPinv has mixed linkages in the backbone containing (1 → 6)-Gal (25.5%), (1 → 4)-Glc (18.3%), (1 → 6)-Glc (8.3%), (1 → 3)-Glc (5.3%) and (1 → 2)-Xyl (4.5%). GIPinv has branching points at (1 → 2, 6)-Man (8.6%) and (1 → 3, 6)-Man (4.9%) having unsubstituted fucose (8.3%) and glucose (16.3%) as terminal sugars. GIPinv had growth-inhibitory activity against several cancer cell lines and triggered apoptosis. GIPinv should be further explored as a potential anti-cancer agent and a unique polysaccharide.